The Influence of Firm Size and Dividend Policy on Stock Price Volatility in the Properties & Real Estate Sector Listed on the Indonesia Stock Exchange - Al-Rasyid, Akhmad Maslan Triananda Surya; Kusumawati, Yulia Tri; Anshari, Rahman (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This think about examines stock cost instability within the property and genuine bequest segment recorded on the Indonesia Stock Trade, centering on two fundamental factors: firm estimate and profit approach. The objective of this inquire about is to decide whether firm measure and profit arrangement impact stock cost instability inside the division. A quantitative approach was utilized utilizing auxiliary information inferred from the yearly money related reports of companies amid the 2023–2024 period. The information were analyzed utilizing different direct relapse. The discoveries show that firm measure contains a critical negative impact on stock cost instability, proposing that bigger companies tend to encounter more steady stock costs. On the other hand, profit approach does not have a critical impact on stock cost instability, suggesting that it isn't however a overwhelming figure in forming speculator discernments when making speculation choices. These comes about infer that firm measure can be considered a chance marker in venture examination, whereas profit approach may not be a essential thought for speculators within the property division.